SOCIAL PROJECT-BASED RELIGIOUS MODERATION LEARNING MANAGEMENT IN FORMING THE CHARACTER OF STUDENTS WITH A GLOBAL INSIGHT - Abu Choir; Zainal Habib; Zainal 'Arifin; Muhammad Shobirin (Nurul Jadid University, 2025)
Religious moderation learning in Islamic educational institutions often focuses on strengthening cognitive aspects through the teaching of normative values rather than on internalising values through reflective social experiences. This study aims to understand how religious moderation learning is managed through social project-based learning to shape students’ character with a global perspective. The study used a qualitative case study design. Data were collected through participant observation, in-depth interviews, and documentation. Data were analysed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that religious moderation is not only taught as a theological concept but is also internalised through the design of social projects integrated into the Islamic boarding school character curriculum, which involve cultural exploration activities, interactions with multireligious communities, ecological activities, and social practices. These findings suggest that social project-based learning can be an innovative pedagogical approach in religious moderation education, while expanding the practice of character education in Islamic boarding schools by connecting religious values, nationality, and global citizenship competencies.